3ln(x+2)-5ln(5x)=x

Simple and best practice solution for 3ln(x+2)-5ln(5x)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ln(x+2)-5ln(5x)=x equation:


Simplifying
3ln(x + 2) + -5ln(5x) = x

Reorder the terms:
3ln(2 + x) + -5ln(5x) = x
(2 * 3ln + x * 3ln) + -5ln(5x) = x
(6ln + 3lnx) + -5ln(5x) = x

Remove parenthesis around (5x)
6ln + 3lnx + -5ln * 5x = x

Reorder the terms for easier multiplication:
6ln + 3lnx + -5 * 5ln * x = x

Multiply -5 * 5
6ln + 3lnx + -25ln * x = x

Multiply ln * x
6ln + 3lnx + -25lnx = x

Combine like terms: 3lnx + -25lnx = -22lnx
6ln + -22lnx = x

Solving
6ln + -22lnx = x

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Combine like terms: x + -1x = 0
6ln + -22lnx + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 | | 47.39=9g+3.92 | | 6+-4+2(6)=14 | | 2(4-8)=16 | | 39+7a=-6(-6a+8) | | 3-2m+3=1-2m+6 | | 14(27-92)=37 | | 90=(3x+6)+(7x+18) |

Equations solver categories